Highly sensitive and selective LPG sensor based on alpha-Fe2O3 nanorods - Patil, Dewyani; Patil, Virendra; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
The alpha-Fe2O3 nanorods were successfully synthesized without any templates by calcining the alpha-FeOOH precursor in air at 300 degrees C for 2 h and their LPG sensing characteristics were investigated. The alpha-FeOOH precursor was prepared through a simple and low cost wet chemical route at low temperature (40 degrees C) using FeSO4 center dot 7H(2)O and CH3COONa as starting materials. The formation of alpha-FeOOH precursor and its topotactic transformation to alpha-Fe2O3 upon calcination was confirmed by X-ray diffraction measurement (XRD). X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. The alpha-Fe2O3 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 1746-50 ppm LPG at 300 degrees C), extremely rapid response (similar to 3-4 s), relatively slow recovery (similar to 8-9 min), excellent repeatability, good selectivity and lower operating temperature (similar to 300 degrees C). Furthermore, the alpha-Fe2O3 nanorods are able to detect up to 5 ppm for LPG with reasonable response (similar to 15) at the operating temperature of 300 degrees C and they can be reliably used to monitor the concentration of LPG over the range (5-60 ppm). The experimental results clearly demonstrate the potential of using the alpha-Fe2O3 nanorods as sensing material in the fabrication of LPG sensors. Plausible LP G sensing mechanism of the alpha-Fe2O3 nanorods is also discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alpha-Fe2O3 nanorods; FESEM; LPG sensor; Semiconductor gas sensors; TEM; XPS; XRD

Humidity-sensing studies of cerium oxide nanoparticles synthesizedby non-isothermal precipitation - Khadse, V. R.; Thakur, Sharada; Patil, K. R.; Patil, Pradip (Sensors and Actuators B-Chemical, 2014)
We report the fabrication of a highly sensitive and fast humidity sensor based on cerium oxide (CeO2) nanoparticles, which were prepared at low cost via a simple non-isothermal precipitation method. The asprepared CeO2 nanoparticles were characterized by X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS) and transmission electron microscopy( TEM) and the results indicated the formation of face centered cubic phase of CeO2 with average crystallite size of approximately 10-12 nm. Humidity sensors based on CeO2 nanoparticles exhibit high and linear response within the whole relative humidity (RH) range of 11-97% at an operating frequency of 60 Hz. The corresponding impedance changes by approximately three orders of magnitude within the entire humidity range from 11% to 97% RH. The response and recovery times are about 2-3 and 9-10 s, respectively, when RH was switched between 11% and 97%. Furthermore, the sensors also show relatively small hysteresis, excellent reproducibility, long term stability and broad range of operation (11-97% RH). The complex impedance spectra of the sensor at different RHs and the equivalent circuit were analyzed to explore the humidity-sensing mechanism. This study demonstrates that the CeO2 nanoparticles prepared by non-precipitation method can be used as the humidity-sensing material for the fabrication of humidity sensors. (C) 2014 Elsevier B. V. All rights reserved.
Keywords: CeO2 nanoparticles; Complex impedance spectra; humidity sensor; Non-isothermal precipitation; TEM